Young Adults' Conceptions of the Sacred in Finland Today. (February 2017) - Ranta, Mette; Pessi, Anne Birgitta; Grönlund, Henrietta
This study examined young adults' perspectives on the concept of the sacred. Altogether, 334 young Finnish adults aged 19–35 were studied through a self-report questionnaire. The participants' personal conceptions, reflections and experiences of the sacred were assessed with open-ended questions. Answers were classified in a data-determined content analysis using a thematic analytical approach. In addition, the study examined how these understandings of the sacred were related to subjective religiosity and how the definitions vary across gender. The findings suggest that the conceptions of the sacred mainly concentrate on individuality and personal issues, including personal opinion, rest and peace, but also close social relationships and the church as an institution. By differentiating the conceptions of the sacred, this study reflects cultural interpretations of what the sacred means and integrates the concept in the theory of young adulthood as a life course phase and in the sociology of youth.